1982
DOI: 10.1113/jphysiol.1982.sp014382
|View full text |Cite
|
Sign up to set email alerts
|

Nervous release of vasoactive intestinal polypeptide from the feline uterus: pharmacological characteristics.

Abstract: SUMMARY1. The release of the neuropeptide, vasoactive intestinal polypeptide (VIP), from the uterus in response to electrical stimulation of the hypogastric and pelvic nerves was examined in non-pregnant anaesthetized cats.2. Efferent stimulation of the pelvic nerve caused an increase in the release of VIP, which was unaffected by atropine and adrenoceptor antagonists, but completely abolished by hexamethonium.3. Efferent stimulation of the hypogastric nerves induced a marked increase in the release of VIP, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In contrast, the present study has extended our previous electrophysiological work (Jobling et al 2003) to demonstrate directly that neurones projecting from mid‐lumbar spinal cord via the lumbar splanchnic and hypogastric nerves provide the major neural pathway for vasodilatation of pelvic arteries supplying the internal reproductive organs of female guinea‐pigs. This is consistent with reports of hypogastric nerve stimulation but not pelvic nerve stimulation increasing venous outflow and VIP release from the cat uterus (Fahrenkrug & Ottesen, 1982). The relative large magnitude of vasodilatations produced by stimulation of the ipsilateral hypogastric or lumbar splanchnic nerves compared with the L3 ventral roots is likely to reflect the extensive bilateral projection of lumbar preganglionic neurones down both hypogastric nerves (McLachlan, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the present study has extended our previous electrophysiological work (Jobling et al 2003) to demonstrate directly that neurones projecting from mid‐lumbar spinal cord via the lumbar splanchnic and hypogastric nerves provide the major neural pathway for vasodilatation of pelvic arteries supplying the internal reproductive organs of female guinea‐pigs. This is consistent with reports of hypogastric nerve stimulation but not pelvic nerve stimulation increasing venous outflow and VIP release from the cat uterus (Fahrenkrug & Ottesen, 1982). The relative large magnitude of vasodilatations produced by stimulation of the ipsilateral hypogastric or lumbar splanchnic nerves compared with the L3 ventral roots is likely to reflect the extensive bilateral projection of lumbar preganglionic neurones down both hypogastric nerves (McLachlan, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, reflex or psychogenic erections in male rats also occur predominantly via sacral outflow through the pelvic nerve (Cruz et al, 1999;Giuliano et al, 1997). However, release of VIP-IR from the feline uterus occurs following both pelvic and hypogastric nerve stimulation (Fahrenkrug and Ottesen, 1982). Furthermore, these authors reported that hypogastric, but not pelvic nerve stimulation, was associated with an increase in uterine venous outflow consistent with uterine vasodilation.…”
Section: Vasodilator Neurons Receive Synaptic Input Via Pelvic and Hymentioning
confidence: 94%
“…VIP has been suggested as the mediator of noncholinergic, non-adrenergic vasodilation in several tissues such as the gastrointestinal tract (Fahrenkrug et al 1978b), the salivary glands (Bloom & Edwards 1980, Lundberg et al 1980, Uddman et al 1980b, the nasal mucosa (Lundberg et al 1981), the tongue (Lundberg et a1.1982b) and the female genital tract (Fahrenkrug & Ottesen 1982). It is also a potent coronary vasodilator (Smitherman et al 1982).…”
mentioning
confidence: 99%